Rare Case Botryoid Rhabdomyosarcomas of the Genital Tract. About a case in a 30-month-old child - M Lahfaoui; H Benhaddou (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Rhabdomyosarcomas are the most common soft tissue sarcomas developed in children under 15 years of age. The reported finding is a vaginal tumour developed in a 30-month-old granddaughter. This was a typical botryoid rhabdomyosarcoma that usually occurs in the hollow organs lined with mucous membrane. Rhabdomyosarcomas have multiple aspects that vary according to the degree of cellular differentiation. The majority of these tumours can be classified into four histological categories: embryonic, botryoid, alveolar or pleomorphic. Treatment involves excisional surgery combined with radiotherapy and chemotherapy. The prognosis remains bleak despite therapeutic advances in recent years.